Online learning performance impact among higher education students in the United Arab Emirates - Alketbi, Sareea Abdulla Ali Bunawas (2023)
In the United Arab Emirates, there are many issues of concern that arise from students’ use of online learning in terms of its effect on learning performance. Prior to the Covid-19 pandemic, online learning was seen as the inevitable future of education, and institutions must be prepared to embrace such technology. Although the United Arab Emirates is one of the leading countries in the Arab world and the region in many indicators, their higher education and training are among the lowest in the Arab region. According to the world competitiveness report 2020, the UAE has ranked significantly well in most of the indicators among 63 countries except for training and education where it ranked 44 out of 63. This implies that the country faces great challenges in producing a workforce with a high-quality education. This research is an attempt to understand online learning in UAE in public higher education institutions by identifying the factors that influence the implementation and adoption of online learning and how it affects student performance. The model consists of six constructs namely overall quality, compatibility, actual usage, user satisfaction, cognitive absorption, and performance impact. The population of this study is the students of the three public universities in the UAE. Moreover, Analysis of the collected data is done in two stages: descriptive statistics are undertaken using SPSS V.26.0 to analyze central tendency and variation statistics. Structural equation modeling, SMART PLS 3.0 is used to test and analyze the main hypotheses and causal relationships among variables. Results found that five variables play an important role to determine the performance impact of online learning namely overall quality, compatibility, user satisfaction, actual usage, and cognitive absorption. The findings of this study can provide public higher education institutions with important insights on how to successfully design and implement online learning within public universities, and how to encourage university boards to ensure that students are more likely to utilize online learning and thereby enabling a better quality of education, wider reach of higher education, gives students more control over their daily tasks and enhances their academic performance.